Eksplorasi Adaptasi Okupasional yang dilakukan oleh Mahasiswa Okupasi Terapi Poltekkes Surakarta yang berasal dari Daerah dengan Kultur Budaya yang Berbeda - Santoso, Tri Budi; Harumi, Linda (Politeknik Kesehatan Kemenkes Surakarta, 2025)
Background: University students, especially those in demanding programs like occupational therapy, often face significant academic pressure, social obligations, and complicated personal responsibilities. This situation presents major obstacles to managing time effectively and achieving a healthy work-life balance. In this context, life balance refers not merely to an equal distribution of time between academic work and personal life, but rather to an individual's subjective perception of fulfilling their needs across various life domains, including academics, social life, recreation, and personal well-being (Greenhaus et al., 2003; Marks & MacDermid, 1996).This study examines the time management patterns of occupational therapy students and how these patterns influence their perception of life balance. Objectives: This study is supposed to investigate time management and life balance among occupational therapy students. Methods: This qualitative study involved 6-8 participants who met the following criteria: (1) aged 18-24 years, (2) currently enrolled as active students (not on academic leave) at Poltekkes Surakarta, and (3) willing to participate as research respondents. Results: The majority of interviewed students reported difficulties in managing their time to achieve life balance, with challenges arising from both internal and external factors. Conclusion: Students need to develop effective time management skills and prioritize important activities to achieve a healthy and balanced lifestyle. Keyword: Life balance, time use, students